Determination of Supplying Ways of Breeding Animals for Sheep Enterprises in Ordu Province - Sezai Alkan; Zeki Türkmen (Turkish Journal of Agriculture: Food Science and Technology, 2020)
In this study, it was aimed to determine the ways of supplying breeding animals for sheep enterprises in Ordu. In the research, enterprises with a minimum size of 80 heads have been taken into consideration. Random selection method was used in determining the enterprises and face-to-face surveys were conducted in 86 enterprises. 37.21% of the enterprise owners met their breeding coach needs from their own enterprises, while 33.72% met from their own enterprise + neighboring enterprises. Moreover, it was determined that 52.33% of the enterprise owners met their breeding female animal needs from their own enterprise, whereas 22.08% and 12.79% met from their own enterprise + neighboring enterprise and from their own enterprise + state enterprise, respectively. According to the results, 58.14% of breeders (50 enterprises) keep breeding female animals for more than 5 years in the herd and 41.86% of breeders (36 enterprises) keep them between 3-5 years. Breeding male animals are kept in the herd for more than 5 years in 47.67% of enterprises (41 enterprises) and for 3-5 years in 41.86% of enterprises (36 enterprises). In only 10.47% of enterprises, breeding male animals are used in the herd as breeding for less than 3 years.